Apakah Etos Kerja Memediasi Pengaruh Pembinaan terhadap Keberhasilan Usaha Mustahik? Studi Empiris pada Penerima Zakat Produktif di Kota Banda Aceh - Al Munawir; Azharsyah Ibrahim; Muhammad Arifin (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2024)
Poverty remains a critical issue requiring strategic and effective solutions. In Aceh, ultra-micro entrepreneurs face significant challenges in obtaining business capital from financial institutions, often resorting to high-interest loans from moneylenders. The Baitul Mal Aceh addresses this problem through the productive zakat program as a tool for poverty alleviation. This study analyzes the impact of coaching and mentoring on the success of mustahik businesses, mediated by work ethic variables. A quantitative research approach was employed, targeting productive zakat recipients of ultra-micro business capital assistance in Baitul Mal Aceh. A sample of 100 respondents was selected, and data were collected using questionnaires. The analysis was conducted using the Partial Least Square (PLS) method with SmartPLS version 3 software. The results reveal: (1) Coaching significantly and positively influences mustahik business success; (2) Mentoring significantly and positively influences mustahik business success; (3) Coaching significantly and positively influences work ethic; (4) Mentoring significantly and positively influences work ethic; (5) Work ethic significantly and positively influences mustahik business success; (6) Coaching significantly and positively influences mustahik business success through work ethic as a mediating variable; (7) Mentoring significantly and positively influences mustahik business success through work ethic as a mediating variable. These findings provide actionable insights for Baitul Mal Aceh in developing economic empowerment programs for mustahik and encouraging them to enhance their work ethic for entrepreneurial success.